Globalization, Academic Migrants and Education: Case Study of Palestine Scholars in India - Tanjeel Ahmed (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
The Israel-Palestine conflict is one of the most complex issues in nature; the issues of sovereignty, territorial issues, and much more are still unresolved in the Israeli-Palestine conflict. More specifically, this ongoing conflict had affected the Palestinians' life, identity, psychology, and development. A thorough literature review reveals that there is an absence of scholarly research in the area of academic migration of Palestinian scholars about the educational challenges in Indian universities. This research uses a qualitative approach with case study methods. The researcher used field study and Snowball Sampling methods to select the study samples. The in-depth perception of six cases was analyzed on the issues of their stay in India, educational challenges in universities, a pedagogical transaction in the classroom, and the different cultural contexts (of their home country and destination country). The study revealed the academic disparities they face about language were problematic, and this hampered the conversation. Critically understanding the international scenario and position of the Palestinian scholars, this research study will contribute to the development of an empathetic understanding of the students from different conflict zones.